Effleurage Massage and Acupressure's Effectiveness in Reducing Labor Pain in Active Phase of First-Stage Labor at Tembilahan Hulu Health Center, Riau - Astuti, Haryati; Syafriani, Syafriani (Journal of Health and Nutrition Research, 2025)
Uterine contractions cause labor pain in the first stage and can be alleviated through non-pharmacological methods like effleurage massage and acupressure. This study aims to evaluate the effectiveness of effleurage massage and acupressure in reducing labor pain and improving labor efficiency. This analytical experimental study used an RCT design with 30 participants, and data were analyzed using univariate and bivariate analysis with the ANOVA test. Both interventions significantly reduced labor pain during the first active phase of labor. The intervention group receiving a combination of effleurage massage and acupressure showed a more significant reduction in pain, with mean scores increasing from 2.27 (SD = 0.799) to 2.73 (SD = 0.594) and significant mean differences (3.44; 95% CI: 3.04–3.85 and 3.22; 95% CI: 1.79–2.88), with F-counts of 8.870 and 9.820 (p = 0.03). In the control group receiving acupressure alone, the mean scores decreased from 3.07 (SD = 0.799) to 2.93 (SD = 0.704), with mean differences of 2.33 (95% CI: 1.79–3.77) and 3.20 (95% CI: 2.64–3.76), F-counts of 8.310 and 9.034 (p = 0.02 and p = 0.01, respectively). The combination therapy proved more effective than acupressure alone in mothers giving birth in the first active phase